EFFORTS TO COMBAT MONEY LAUNDERING (RESEARCH STUDY OF MEDAN POLRESTABES) - Yasmirah Mandasari Saragih; Ilmuwani Lubis; Karolus Agung Dery Rianto; Irfan Rizky Pradya; Willy Novan Prakoso (RADJA PUBLIKA, 2023)
Money laundering, often known as money laundering, is carried out by government officials who hold the power to roll back money that is not legitimate after getting proceeds that are not theirs. In Indonesian, money laundering is translated by the term